Development of axial fan with contraction nozzle for Perpetual Motion Energy Harvesting System - Aldhufairi, Mohammed M A S (2022)
Nowadays, renewable energies are highly demanded as they are sustainable and environmentally friendly. One of the renewable energy is wind, and it can be harvested by using a wind turbine. However the power generated in any system by natural phenomenon has lots of limitations because of the inconsistency in the supply of the energy by the source. Wind energy from nature environment has limitation and inconsistency. Sometimes there are wind energy and sometimes no wind energy. It is mandatory to design a system which produces continuous and repeated power for the effective use. Also, in some parts of the country the weather is unpredictable to apply wind turbine system because of the environment. Hence, the research aimed to design and develop axial fan with contraction nozzle for Perpetual Motion Energy Harvesting System. The study focused on the design of a new concept to improve the energy harvested of wind turbines to be appropriate for the unpredictable wind energy condition in Malaysia. The concept involves the implementation of axial turbine fan and concentrator nozzle for Perpetual Motion Energy Harvesting System, to increase the electricity generated. Although the system used electricity to start, the implementation of the fan and nozzle should contribute to improve the electricity harvested by wind turbine system so that the harvested electricity can cover the used electricity in the system. Before the configuration of fan and nozzle were fabricated, the concept of axial fan was studied to get the best performance and then the nozzle was simulated with the use of a program to obtain the high wind speed in the system. Next the axial fan and contraction nozzle were fabricated and tested. Results showed that axial fan can produced wind energy with average speed of 3.6 m/s while the contraction nozzle improved the wind speed at outlet which average is 4.7 m/s. Then the integrated axial fan and contraction nozzle were verified for perpetual motion energy harvesting system by analysed the rotation speed of wind turbine and the output voltage of the turbine generator. The maximum output voltage that can be generated by perpetual motion energy harvesting system was 3.7 V using integrated axial fan and contraction nozzle. The voltage was measured using digital multimeter